Understanding the link between gendered access to agricultural land and household nutrition outcomes in the Democratic Republic of Congo (DRC) - Janvier Mwisha-Kasiwa; Cédrick Kalemasi Mosengo; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2023)
Using data from the DRC Demographic and Health Survey, this study examines the empirical linkages between access to agricultural land and nutritional outcomes by examining gender differences. Results suggest significant effects of access to agricultural land on nutritional outcomes in the full sample, in the male and female-headed households' subsamples as well. However, gender differences are reported. Access to agricultural land appears to be a significant determinant of improved children dietary diversity among female-headed households (FHH), it is also associated with a significant increase in the children height-for-age z-score in the maleheaded households (MHH). Moreover, access to agricultural land positively affects the women's likelihood of having a normal body mass index the male-headed households; and finally, the study finds that accesses to agricultural land is linked with a significant decrease in the risk of women anaemia among the female-headed households. Since then, we argue that access to agricultural land by MHHs may be beneficial for long-term nutrition indicators while it is more beneficial for short-term nutrition measures among FHHs.
Keywords: C35; D13; I12; J16; Q12; Q15; 330; Access to agricultural land; dietary diversity; nutrition status; gender; DRC